A multi-scalar study of the long-term reactivity of uranium mill tailings from Bellezane site (France). (July 2020) - Ballini, M.; Chautard, C.; Nos, J.; Phrommavanh, V.; Beaucaire, C.; Besancon, C.; Boizard, A.; Cathelineau, M.; Peiffert, C.; Vercouter, T.; Vors, E.; Descostes, M.
Abstract: The mill tailings from uranium mines constitute very low-level, long-lived, radioactive process waste. Their long-term management therefore requires a good understanding of the geochemical mechanisms regulating the mobility of residual uranium and radium-226. This article presents the results of the detailed characterization of the tailings resulting from the dynamic leaching processes used on the ore of the La Crouzille mining division and stored at the Bellezane site (Haute-Vienne, France) for over 25 years. A multi-scalar and multidisciplinary approach was developed based on a study of the site's history, on the chemical, radiological and mineralogical characterizations of the solid fraction of the tailings, and on porewater analyses. These were complemented by thermodynamic equilibrium models to predict the long-term mobility of U and 226 Ra. Weakly acidic (pH = 6.35) and oxidizing (Eh = 138 mV/SHE) porewaters had a sulfated-magnesian facies ([SO4 ]tot = 43 mmol/L; [Mg]tot = 33 mmol/L) with an accessory calcium bicarbonate component (TIC = 25 mmol/L; [Ca]tot = 13 mmol/L) and dissolved concentrations of uranium and 226 Ra of 12 × 10 −6 mol/L and 0.58 Bq/L respectively. Ultra-filtration at 10 kDa indicated the absence of colloidal phases. The characterization of the tailings confirmed their homogeneity from a radiological, chemical and mineralogical point of view. The residual U and 226 Ra concentrations measured in the solid were 160 ppm and 25 Bq/g respectively, in accordance with the initial ore grades and mill yields, or more than 99% of the total stock. In terms of chemical and mineralogical composition, the tailings were mainly composed of minerals from the granitic ore (quartz, potassium feldspar, plagioclases and micas) in association with their weathering products (smectite and ferric oxyhydroxides) and with neo-formed minerals following rapid diagenesis after neutralization of the tailings before their emplacement (gypsum and barite). All these minerals are effective traps for the retention of U and 226 Ra. The uranium is distributed partly in micrometer scale uraninite and coffinite refractory phases embedded in grains of quartz, and partly sorbed to smectite and ferric oxyhydroxides. The 226 Ra on the other hand is trapped mainly within the barite. The aqueous concentrations of U and 226 Ra could be described using a thermodynamic approach so that their long-term mobility can subsequently be assessed by modeling. The paragenesis of the tailings could be seen to be stable over time with the exception of neo-formed gypsum and calcite, which will gradually dissolve. The presence of retention traps offering surplus capacity, i.e. smectite, ferric oxyhydroxides and barite, will maintain the U and the 226 Ra at very low aqueous concentrations, even under oxidizing conditions. Moreover, the low permeability of the mill tailings leads, in the case of 226 Ra, to behavior dictated only by the radioactive decay. Graphical abstract: Image 1 Highlights: U mill tailings from Bellezane (France) were studied 25y after their deposition (81 characters). U and 226 Ra are immobile through retention process (50 characters). U mobility is constrained by sorption onto smectite and ferrihydrite (70 characters). 226 Ra mobility is governed by coprecipitation into barite and radioactive decay (81 characters).